Pengaruh Penerapan Pendekatan Matematika Realistik Indonesia (PMRI) Terhadap Disposisi Matematika Siswa Pokok Bahasan Komposisi Dua Fungsi Dan Invers Fungsi Di Kelas XI IA-1 SMAN 4 Padangsidimpuan - Safitri, Adek (IAIN PADANGSIDIMPUAN, 2019)
The objective of this study is to determine the effect of the application of the mathematical realistic approach toward the students’ mathematics disposition. This study used a pre-experimental research design with a sample cluster random sampling technique. The experiment was conducted in SMA Negeri 4 Padangsidimpuan with the overall population of students of class XI IA second semester of the 2011/2012 academic year which consist of 5 classes as many as 163 students, while the sample of this study was class XI IA-1 which consist of 31 students. The instrument used the validated questionnaire. The experiment class was given pretest before treatment and posttest after treatment. Learning by using realistic mathematics approach provided significant influence on students' mathematical disposition. This was indicated by t-test were obtained t-hitung = 9.8 and t-tabel = 2.042. The data fulfilled the test of the hypothesis which is if t-hitung ≥ t-tabel then H0 is rejected and H1 is accepted, which means there was a significant influence of the application of mathematical realistic approach Indonesia (PMRI) toward the students’ mathematics disposition at class XI IA-1 SMAN 4 Padangsidimpuan.